IMPLEMENTASI SISTEM LAYANAN PERIZINAN TERPADU (SILAT) DI KANTOR DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU - Tamario Sutan; Dila Novita (Governance, 2022)
Basically, public services include three aspects, namely goods, services and administrative services. One form of administrative service is licensing. The community must obtain services that are easy, cheap, fast, and friendly in order to achieve the desired public satisfaction. Through the Integrated Licensing Service System (SILAT) there are innovations in service methods, namely new changes in the way of providing licensing services to the community and also new changes in the way of interacting between actors involved in services. The purpose of this study is to analyze the implementation of the One Stop Integrated Licensing Service System (SILAT) at the Bekasi City Investment Service and One Stop Integrated Services and evaluate the obstacles faced in implementing the One Stop Integrated Licensing Service System (SILAT) at the Investment Service and One Stop Integrated Service for Bekasi City. This research method is qualitative with a case study research design, data collection techniques using observation and in-depth interviews with purposive sampling technique to determine informants. The results of this study state that the implementation of the Integrated Licensing Service System (SILAT) at the Bekasi City Investment and One Stop Services Office (DPMPTSP), started on August 8, 2017. The implementation of the integrated licensing service system (SILAT) is still experiencing many obstacles. Many Bekasi City people still do not understand the Online-Based Integrated Licensing Service System. In addition, there are still many people who do not understand the mechanism of online licensing and there is also a lack of socialization from the government, especially the Investment Service and One Stop Integrated Service regarding the integrated licensing service system (SILAT).